PEMANFAATAN SAMPAH ORGANIK SEBAGAI PRODUK EKO-ENZIM WASTE ORGANIC PRODUCT (WOP) FST 1310 - Hamada, Firdaus Ramadhan (Institut Sains dan Teknologi Nasional, 2025)
Waste Organic Product (WOP) FST 1310 is an eco-enzyme product made by Faculty of Science and Technology (FST) Team of UIN Syarif Hidayatullah to reduce organic waste around the college environment. This product is made with orange peel (WOP FST 1310 KJ) and vegetable residue (WOP FST 1310 SY). Each of these ingredients is combined with water and molasses in a ratio of 3:10:1, then fermented for 90 days. Based on the organoleptic test, after 90 days of fermentation, there was a change in the sense of smell, which started with the aroma of ingredients (orange peel and vegetables) to becoming sweet and sour, typical of fermentation. Color change from light brown to dark brown is accompanied by a slight precipitate. Results of measuring the chemical-physical properties of the product were acidic pH (3.4 for WOP FST 1310 KJ and 4.4 for WOP FST 1310 SY). TDS and turbidity parameters for product are 3325 ppm and 3780 ppm; 683 FTU and 897 FTU), respectively. WOP FST 1310 product has the same properties as eco-enzymes in general based on organoleptic tests and measurements of chemical-physical properties. Keywords: Eco-enzyme, Organic Waste, Orange Peel, Vegetable, WOP FST 1310